2017
DOI: 10.3847/1538-4357/834/1/72
|View full text |Cite
|
Sign up to set email alerts
|

Two Long-Term Intermittent Pulsars Discovered in the Palfa Survey

Abstract: We report the discovery of two long-term intermittent radio pulsars in the ongoing Pulsar Arecibo L-band Feed Array survey. Following discovery with the Arecibo Telescope, extended observations of these pulsars over several years at Jodrell Bank Observatory have revealed the details of their rotation and radiation properties. PSRs J1910+0517 and J1929+1357 show long-term extreme bimodal intermittency, switching between active (ON) and inactive (OFF) emission states and indicating the presence of a large, hithe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 36 publications
2
39
0
Order By: Relevance
“…The percentage polarization in pulsars is high usually exceeding 60% in the highĖ range, but decreases near the transition region to less than 20% and subsequently increases slightly to around 30% for lowerĖ pulsars. Additionally, the five pulsars which show intermittent behaviour, i.e where the radio emission vanishes for long durations, all lie in this narrowĖ range (Lyne et al 2017). Of the three pulsars J0826+2637, J0946+0951 and J1825-0935, where detailed simultaneous radio and X-ray studies have been carried out the first two showed synchronous variations.…”
Section: The X-ray Variation During the Different Emission Modesmentioning
confidence: 83%
See 1 more Smart Citation
“…The percentage polarization in pulsars is high usually exceeding 60% in the highĖ range, but decreases near the transition region to less than 20% and subsequently increases slightly to around 30% for lowerĖ pulsars. Additionally, the five pulsars which show intermittent behaviour, i.e where the radio emission vanishes for long durations, all lie in this narrowĖ range (Lyne et al 2017). Of the three pulsars J0826+2637, J0946+0951 and J1825-0935, where detailed simultaneous radio and X-ray studies have been carried out the first two showed synchronous variations.…”
Section: The X-ray Variation During the Different Emission Modesmentioning
confidence: 83%
“…On the other hand a separate class of emission properties have emerged which seem to be pan-magnetospheric. These include the intermittent behaviour in pulsars which show changes in period derivatives during long nulling intervals lasting from weeks to months (Kramer et al 2006;Lyne et al 2017), the transition of the pulsar between different emission modes, including long duration null modes, with modal durations from several hundred periods to several hours at a time, the periodic intensity modulations with durations of 10-100 periods, amongst others. The pan-magnetospheric nature of the later two phenomena, mode changing and periodic intensity modulation, is highlighted by the interaction between the main pulse and the interpulse which appear to be simultaneously affected during these changes.…”
Section: The Relation Between the Radio Emission From The Two Polesmentioning
confidence: 99%
“…The lack of any detection of PSR J1831−04 since its initial discovery suggests that it may belong in the class of so-called 'intermittent' pulsars whose 'off' timescales may range from hours to days and even years, and of which only a handful of examples are currently known (see e.g. Kramer et al 2006a;Camilo et al 2012;Lorimer et al 2012;Lyne et al 2017). As our understanding of the nulling timescales of PSR J1812−15 still remains incomplete, it is possible that this pulsar may also qualify as intermittent, with non-detections sometimes appearing to last longer than the pulsar's typical integration time (∼ 10 − 30 min).…”
Section: Psr J1706-4434 a Glitching Pulsarmentioning
confidence: 99%
“…Analysis of their burst arrival times reveals underlying regularity of the order of seconds and they have comparable spindown rates to other neutron star classes. A group known as intermittent pulsars go through a quasiperiodic cycle between phases in which radio emission is and is not detected (Kramer et al 2006;Camilo et al 2012;Lorimer et al 2012;Lyne et al 2017) with timescales of variability ranging from weeks to years. The intermittent pulsar discovered by Kramer et al was the first example of a pulsar showing emission changes that were strongly linked to rotational behaviour.…”
Section: Introductionmentioning
confidence: 99%